The Relation of Angiotensin Converting Enzyme-1 Gene with Angiotensin II and Plasminogen Activator Inhibitor in Myocardial Infarction - Maha F. Smaism (Journal of Global Pharma Technology, 2017)
One of the very important causes of mortality worldwide is myocardial infarction (MI). Angiotensin converting enzyme-1 (ACE-1) gene plays a principal role in converting of angiotensin-I (ANG I) to angiotensin II (ANG II). ANG II plays necessary role in promoting of hypertension, furthermore due to the improvement of cardiovascular disease, myocardial infarction. Plasminogen activator inhibitor-1(PAI-1) play a function in modulating intravascular thrombosis, impaired fibrinolytic linked to a high level of (PAI-1).The aim of the study is to evaluate the role of ACE-1polymorphism in level of ANG II, and the relation between plasminogen activator inhibitor-1concentration and ANG II in (MI) and hypertension patients. The study includes (100) males: 25 control, 75 patient groups, the patient group subdivided into 25 hypertensive patients for 10 years (group A), 25 hypertensive patients for 20 years(group B), 25 patients with MI+ hypertension ( group C), ages between (50-60 years) and BMI (18.5-24.9).The results show: There is significantly increased of ANG II, PAI-1, TG, Total cholesterol(TC), LDL-c and VLDL-c concentration, while significantly decreased of serum HDL-c in all groups of patients compared with the control group. The result observed significantly increase of ACE-1 deletion –deletion (DD)in group (C) (88%) compared with the control group (44%), while there were no significantly increased in groups (A,B) compared with control group, also the result showed ACE-1 (DD) genotype was (66%), insertion-deletion (ID) genotype was (34%) and ACE insertion-insertion( II )genotype was (0%) in all study groups. And there was a positive correlation between angiotensin II and plasminogen activator inhibitor-1 in all patient groups. Conclusion: The (DD) genotype of the Angiotensin converting enzyme-1 (ACE-1) polymorphism was the most frequent among Babylon patients with myocardial infarction. This suggests that Babylon individuals with the (DD) genotype might be at high risk for myocardial infarction .Furthermore, D allele of the ACE I polymorphism might confer increased risk for MI. plasminogen activator inhibitor 1(PAI-1) may consider as a risk factor of myocardial infarction. And there was a positive correlation between angiotensin II and plasminogen activator inhibitor-1 in all patient groups. Therefore DD genotype be lead to an increase of PAI-1level.Keywords: Myocardial infarction, Angiotensin converting enzyme-1, Plasminogen activator inhibitor-1, Angiotensin II.